2022
DOI: 10.30872/psikostudia.v11i3.7021
|View full text |Cite
|
Sign up to set email alerts
|

Pentingnya Perencanaan Karier Terhadap Pengambilan Keputusan Karier

Abstract: The results of previous studies have shown that career planning has proven effective in improving career decision-making in vocational, junior high, and age students, but there has been no research that examines the relationship between career planning and career decision making in high school students. This study aims to determine the relationship between career planning and career decision making for high school students. The type of research used is quantitative research. The study population is students of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…Based on the results of research that has been conducted by researchers, it is found that career planning has a positive effect on the career decisions of final year students. These results are in line with research conducted by (Ayu et al, 2022) where there is a positive and strong relationship between career planning and career decision making. The same thing with research conducted by (Walidaini, 2022) which states that students who have knowledge and experience in honing skills, give them confidence in choosing and deciding on their careers.…”
Section: The Effect Of Career Planning On Final Year Student Career D...supporting
confidence: 91%
See 1 more Smart Citation
“…Based on the results of research that has been conducted by researchers, it is found that career planning has a positive effect on the career decisions of final year students. These results are in line with research conducted by (Ayu et al, 2022) where there is a positive and strong relationship between career planning and career decision making. The same thing with research conducted by (Walidaini, 2022) which states that students who have knowledge and experience in honing skills, give them confidence in choosing and deciding on their careers.…”
Section: The Effect Of Career Planning On Final Year Student Career D...supporting
confidence: 91%
“…In practice, decision making cannot only rely on confidence in one's abilities but can be enhanced by career planning. During this process, there is an inventory of values, interests, personality, and skills starting from oneself so that individuals can make a career list data according to what is known about oneself (Ayu et al, 2022). Family support was chosen as a moderating variable because as said by Zhang et al (2015) that the higher the parental support for an individual's career, the higher their self-efficacy in making career decisions.…”
Section: Introductionmentioning
confidence: 99%